Does respiratory syncytial virus subtype influences the severity of acute bronchiolitis in hospitalized infants? - Papadopoulos, N. G.; Gourgiotis, D.; Javadyan, A.; Bossios, A.; Kallergi, K.; Psarras, S.; Tsolia, M. N.; Kafetzis, D. (Respir Med, 2004)
Respiratory syncytial virus (RSV) subtypes A and B are present either simultaneously or alternate during yearly epidemics. It is still not clear whether clinical severity of acute bronchiolitis differs between the two subtypes. Reverse transcription polymerase chain reaction was used to subtype RSV in previously healthy infants hospitalized with RSV bronchiolitis during a winter epidemic. A severity index based on heart rate, respiratory rate, wheezing, difficulty in feeding and oxygen saturation was calculated upon admission. Infants infected with RSV subtype-A were found to have a significantly higher (more severe) clinical score than those infected with RSV-B. There was no statistically significant difference in duration of hospitalization or need of intensive care. Boys and infants younger than 3 months of age were also more severely affected than girls or older infants, respectively. These results support the notion that RSV-A-induced bronchiolitis is more severe than RSV-B-induced one, in agreement with the majority of previously published studies.
Keywords: Acute Disease Age Factors Bronchiolitis Female Hospitalization Humans Infant Infant; Human Severity of Illness Index Sex Factors; Newborn Intensive Care Length of Stay Male Respiratory Syncytial Virus Infections Respiratory Syncytial Virus